Is the “Common Cold” Our Greatest Ally in the Battle Against SARS-CoV-2? - Capoor, Manu N.; Ahmed, Fahad S.; McDowell, Andrew; Slaby, Ondrej (Frontiers in Cellular and Infection Microbiology, 2020)
The discovery of T-cell responses to SARS-CoV-2 in non-infected individuals indicates cross-reactive immune memory from prior exposure to human coronaviruses (HCoV) that cause the common cold. This raises the possibility that ‘immunity’ could exist within populations at rates that may be higher than serology studies estimate. Beside specialized research labs, however, there is limited ability to measure HCoV CD4+ and CD8+ T-cell responses to SARS-CoV-2 infection, which currently impedes interpretation of any potential correlation between COVID-19 disease pathogenesis and the calibration of pandemic control measures. Given this limited testing ability, an alternative approach would be to exploit the large cohort of currently available data from which statistically significant associations may be generated. This would necessitate the merging of several public databases including patient and contact tracing, which could be created by relevant public health organizations. Including data from both symptomatic and asymptomatic patients in SARS-CoV-2 databases and surveillance systems could provide the necessary information to allow for more informed decisions.